Impact of Quorum Sensing and Tropodithietic Acid Production on the Exometabolome of Phaeobacter inhibens - Srinivas, Sujatha; Berger, Martine; Brinkhoff, Thorsten; Niggemann, Jutta (Frontiers in Microbiology, 2022)
Microbial interactions shape ecosystem diversity and chemistry through production and exchange of organic compounds, but the impact of regulatory mechanisms on production and release of these exometabolites is largely unknown. We studied the extent and nature of impact of two signaling molecules, tropodithietic acid (TDA) and the quorum sensing molecule acyl homoserine lactone (AHL) on the exometabolome of the model bacterium Phaeobacter inhibens DSM 17395, a member of the ubiquitous marine Roseobacter group. Exometabolomes of the wild type, a TDA and a QS (AHL-regulator) negative mutant were analyzed via Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). Based on a total of 996 reproducibly detected molecular masses, exometabolomes of the TDA and QS negative mutant were ~70% dissimilar to each other, and ~90 and ~60% dissimilar, respectively, to that of the wild type. Moreover, at any sampled growth phase, 40-60% of masses detected in any individual exometabolome were unique to that strain, while only 10-12% constituted a shared ‘core exometabolome’. Putative annotation revealed exometabolites of ecological relevance such as vitamins, amino acids, auxins, siderophore components and signaling compounds with different occurrence patterns in the exometabolomes of the three strains. Thus, this study demonstrates that signaling molecules, such as AHL and TDA, extensively impact the composition of bacterial exometabolomes with potential consequences for species interactions in microbial communities.